Characterization of droplet sizes in large scale oil–water flow downstream from a globe valve. (February 2018) - Paolinelli, L.D.; Rashedi, A.; Yao, J.
Highlights: Water-in-oil dispersions produced in a globe valve are studied. Measured maximum droplet sizes correlate with classic turbulent break-up models. Maximum and mean droplet sizes increase with the dispersed phase volume fraction. Droplet size distributions shift to lower sizes and narrow with the pressure drop. Abstract: Oil–water dispersed flows produced at valves or restrictions are very common in industry. For example, crude oil desalting processes normally use dispersion valves to mix the dilution water. In this case, the knowledge of dispersed droplet sizes is crucial for the design and optimum control of the process. However, little work has been devoted to characterize and model droplet sizes produced in industrial-type valves. The present work studies water droplet sizes produced by the passage of oil–water flow through a globe valve mounted in a large scale flow loop of 0.1 m internal diameter. Experiments were performed under different pressure drops across the globe valve, and different oil and water flow rates. Produced water droplet sizes were measured in situ downstream from the globe valve location using particle video microscopy. Droplet sizes were compared with theoretical scales for turbulent and viscous break-up. The effect of the volume fraction of dispersed phase on droplet size was also examined. In addition, droplet size distributions were analyzed and fitted using known statistical functions.